Fungal Pulmonary Valve Endocarditis Masquerading as a Pulmonary Embolism - Kevin B. Ricci; Peter H. U. Lee; Michael Essandoh; Ahmet Kilic (Case Reports in Surgery)
Septic pulmonary emboli (SPE) can be a difficult clinical entity to distinguish from thromboembolic pulmonary embolism (TPE) in a patient with history of IV drug abuse (IVDA). We present a case of a patient who presented with failure to thrive and presumed diagnosis of recurrent PE that ultimately was discovered to have fungal pulmonary valve endocarditis resulting in a right ventricular outflow obstruction. This required replacement of the pulmonary valve and repair of the right ventricular outflow tract. This case highlights difficulty in differentiating pulmonary valve endocarditis with septic emboli from chronic PE in a patient with a complex medical history.